Quality Improvement Initiative Implementation at the Unit or Hospital Level - Colley, Alexis; Wick, Elizabeth (Clinics in Colon and Rectal Surgery, 2023)
Quality improvement efforts take considerable commitment, including mentorship, training, and resources. Leveraging an established framework, such as that outlined by the American College of Surgeons, to design, implement, and analyze quality improvement projects offers the best chance for success. Herein, we illustrate the application of this framework to a gap in advance care planning for surgical patients. This article helps outline how to go from identifying and outlining a problem, to articulating a clearly defined project goal that is specific, measurable, attainable, relevant, and timebound, and later implementing and analyzing a gap in quality identified at the unit (e.g., service line, inpatient unit, clinic) or hospital level.
Keywords: advance care planning; informatics; resident education; quality improvement